Strategi Komunikasi Pembelajaran Di Rumah Dalam Lingkungan Keluarga Masa Pandemi - Zulkifli Makmur; Muhammad Arsyam; Andi Muhammad Shaleh Alwi (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2020)
The government, in dealing with the Corona Virus Disease (Covid-19) pandemi, has set new policies, such as isolation, social and physical distancing, and large-scale social restrictions (PSBB) that keep people staying, working, worshiping, and studying at home. This study aimed to analyze learning at home in a family environment during the pandemi. The method used was ex-post facto. The causes of the naturally occurring variables were reviewed. The population in this study was all students of the Islamic Religious Education Study Program (PAI) of STAI DDI of Makassar City, as many as 225 students, from which 26 (from semester VI) were taken as the sample using a simple random sampling technique. The results of this research with descriptive statistical analysis and inferential statistical analysis showed that the normality test of the learning-at-home activities showed a value of 1.025 and that of the family environment showed a value of 2.131 (sig>α, normal distribution), the homogeneity test results showed a value of 1.412 (sig>α, homogeneous), the linearity test results showed a value of 0.986 (sig>α, linear), and the activeness and the results of the hypothesis test with the correlation test showed a sig value of 0.023, with the criteria of sig (0.023) of <α (0.05). Finally, this study concluded that there are learning at home in the family environment amid the COVID-19 pandemi.